Skid Resistance of nano silica modified roller compacted rubbercrete for pavement applications: Experimental methods and response surface methodology. Issue 1 (1st January 2018) - Adamu, Musa; Mohammed, Bashar S.; Shafiq, Nasir; Shahir Liew, Mohd
Abstract: Roller compacted concrete (RCC) pavement usage is limited to low-speed roads due to its low skid resistance, caused by the smooth surface texture that makes it unsuitable for use in high-speed traffic pavements. If used in high-speed roadways will lead to increased skid related accidents. In this study, crumb rubber was used as partially replaced with fine aggregate at levels 10, 20, and 30% by volume to produce roller compacted rubbercrete (RCR) so as to improve the skid resistance of RCC pavement, and nano silica was added at 0, 1, 2 and 3% by weight of cementitious materials to mitigate loss of strength with incorporation of crumb rubber. The British Pendulum Number (BPN) was used to measure the skid resistance. Incorporating up to 20% crumb rubber and 2% nano silica increases both skid and impact resistance. The findings showed that RCR with 20% CR and 2% NS can be used for motorways, trunk, and class 1 roads. Finally, response surface methodology was used to develop the relationship between BPN in wet/dry conditions and crumb rubber/nano-silica. The analysis of variance for response surface methodology analysis shows that the quadratic models developed has a very good degree of correlation, and can be used to predict the skid resistance of RCR. The results of multi-objective optimization showed that an optimum mixture can be achieved with a 17.20% volume replacement of fine aggregate and 1.87% nano silica addition by weight of cementitious materials to have the highest skid resistance RCR for pavement applications.